HANDICRAFT ENTREPRENEURSHIP DEVELOPMENT IN THE REPUBLIC OF UZBEKISTAN - Abulkasimov Hasan Pirnazarovich; Abdullayeva Rano Gafurovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
The article analyses craftsmanship development issue in Uzbekistan and developed scientific proposals and practical recommendations for improving the mechanism of the handicraft activities development through the expansion of entrepreneurship.